Use of computer-mediated communication in online discussion forum - Rismi Juliadi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
The purpose of this study is to explore the usage of computer-mediated computer communication in online learning during the COVID-19 pandemic. This study focuses on how Universitas Multimedia Nusantara lecturers and students (UMN) build interaction for online learning. The research methodology used qualitative methods with six informants, and data generation was using in-depth interviews. The results indicated that most students positively perceived the online discussion forum as computer-mediated communication (CMC) in online learning during the COVID-19 pandemic. The students' perceptions are considered negative about lecturers' responses in the discussion forum because lecturers usually are late in replying to the student's questions. Students are satisfied with using computer-mediated communication in E-learning UMN, which has given many benefits in supporting online learning activities. The students need and expect the lecturers that they would have an enthusiastic attitude, provide immediate feedback, select the appropriate topic, and regularly participate in the online discussion forum.